(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the physical chemical parameters of jelly mix from the pulp of cagaita (Eugenia dysenterica) and mangaba (Hancoria speciosa) through analysis of moisture, fat, proteins, ash, acidity, pH, beta carotene, total sugars, solids solubles (ºBrix), vitamin C, total caloric value (VET), total dietary fiber and colorimetry. The jelly was made with 40% of the cagaita pulp and 60% of the mangaba pulp, corresponding to the extra type of jelly (ratio 50:50 parts of pulp and sugar). The pulps were extracted by mechanical pulping using a 1.5 mm sieve. The mix jelly had a pH around 3.2 and was characteristic of a semi-solid jelly. The soluble solids content was 65.75 and the vitamin C constituent was 60.89 (mg 100g-1), proving to be a good source of this vitamin and nutrients.